Enteral nutrition for optimal growth in preterm infants - Myo-Jing Kim (Korean Pediatric Society, 2016)
Early, aggressive nutrition is an important contributing factor of long-term neurodevelopmental outcomes. To ensure optimal growth in premature infants, adequate protein intake and optimal protein/energy ratio should be emphasized rather than the overall energy intake. Minimal enteral nutrition should be initiated as soon as possible in the first days of life, and feeding advancement should be individualized according to the clinical course of the infant. During hospitalization, enteral nutrition with preterm formula and fortified human milk represent the best feeding practices for facilitating growth. After discharge, the enteral nutrition strategy should be individualized according to the infant's weight at discharge. Infants with suboptimal weight for their postconceptional age at discharge should receive supplementation with human milk fortifiers or nutrient-enriched feeding, and the enteral nutrition strategy should be reviewed and modified continuously to achieve the target growth parameters.